Iloilo Province, Philippines coffee bean farming potentials and challenges - Amedo, Vea Alyssa; Balasoto, Josefino Darcy; Dable, Chereene; Luces, Arnicole; Pastrana, Marian Juliene; Tabares, Kirschten Faye. (2017.)
One of the highly traded commodities is coffee. Coffee occupies an important place in the world economy, being widely consumed as the most prestigious beverage. It provides employment to numerous employees and has become an important monetary source in rural areas. Coffee is said to be crucial to the economies and politics of many developing countries. As far as the researcher's knowledge, there is no existing academic literature pertaining to the coffee farming industry in Iloilo Province, particularly on its challenges and potentials. Hence, the researchers would like to make this study to identify and discuss the potentials as well as the challenges of coffee bean farming in Iloilo Province, Philippines. The researchers used mixed approach as their method wherein both qualitative and quantitative approaches were integrated. In the qualitative approach, Interview Questionnaires and Key Informant Interviews (KII) were used as the key instrument to obtain information from the farmers and or land owners of coffee. Then the quantitative approach was used in showcasing the results where it was presented through graphs and charts such as bar graphs, pie charts, radar chart, and tables. It was analyzed using both descriptive and inferential analysis. Out of 23 coffee farmers from the data of Department of Trade and Industry (DTI, only 12 farmers were reached and responded to the invitation of the researchers. Among the 12 respondents, 4 who were interviewed are officers of an Association and the remaining 8 owns their respective coffee farms. Two respondents were interviewed from Janiuay, Calinog, Barotac Viejo, and Lambunao. However, there were only one farmer who was interviewed from San Enrique, Leon, Badiangan, and Barotac Nuevo. Six (6) farmers actually said that profitability depends on the market price and condition but over all, it is still profitable; the reason. behind this occurrence is that when price go down, they will not incur loss only less profit. It will be profitable because coffee is an in-demand commodity which means that with the effective methods, sufficient knowledge and connections through the different networks concerned in the industry, venturing in coffee is a good investment. Through the research process and results, the researchers found out that the challenges in which the farmers are experiencing are: pests, diseases and weeds (i.e. Balagon); low quality of produced; lesser price due to lack of post-harvest processing; planting materials for nursery; lack of post-harvest facilities, internally . Additionally, lack financial support; lack of availability of labor; lack of information/technology dissemination; market price inconsistency; lack of training on specific issues/concerns; lack of sustainable and government support were the external challenges that was found out. On the other hand, the potentials identified were: high market price (i.e. Malls); processed to value-added products; area is suitable for coffee farming; long lifespan of coffee; minimal maintenance; high demand; and profitable. Thus the researchers have recommended the following: there should be a symbiotic relationship between coffee bean farmers and government support agencies; the government should assist the coffee bean farmers in utilizing possible land areas that are suitable for the two varieties of coffee beans- Arabica and Robusta; find a way to shift the mindset and behavior of the farmers in following the standardized production system and perceived purpose of the supports receive; government should provide facilities and input to coffee bean farmers to increase interest; the Iloilo, Province coffee can be branded immediately as Robusta through government agencies, future researchers reference. Through these recommendations, the researchers believe that the government agencies followed by the positive response of the coffee bean farmers will both parties be able to maximize the support system that connects both parties. Also, such suggestions can be employed by private entities as the given commendations were created in the maximization of all the stakeholders in the value chain of the coffee bean farming industry in Iloilo Province, but the focus on government was raised in the fact that most coffee bean farmers rely heavily on government aide. the researchers hope that these stakeholders will be able to achieve their individual plans and goals while still focusing and pursuing the coffee industry roadmap.
Research Paper (Mgt 199-Management Research). -- [Iloilo City] : University of the Philippines Visayas-College of Management, December 12. 2017.